Genesis, mineralogy, and micromorphology of vertic soils in southeastern Kansas - Hartley, Paul Evan (Kansas State University, 2010)
Many soils in southeastern Kansas are characterized by high clay contents and high shrink-swell potentials. Their vertic properties and claypan characteristics cause soil management to be difficult and pose problems for agricultural, environmental, and engineering uses. Thus, collecting more information and improving our understanding of these soils is an important step towards bettering our soil management techniques. The objectives of this study were to examine the morphology, processes of soil genesis, clay mineralogy, micromorphology, and potassium fixation potential of the soils of interest and how these characteristics varied between and within individual pedons. Ten pedons expected to represent varying degrees of vertic expression were selected. Methods included the use of field descriptions, routine soil laboratory characterization, micromorphological investigations, the determination of clay mineralogy by X-ray diffraction, and the measurement of potassium fixation potential. Field morphology reflected the geologic parent materials available in the region. The fine sediments that compose these clayey soils are primarily provided by the Pennsylvanian and Permian shales and limestones underlying this region and the Flint Hills to the west. Dominant pedogenic processes currently at work are clay illuviation and shrink-swell processes. Silty, non-expansive surface soils at all but sites 6 and 7 are thought to buffer the rapid wetting and drying cycles needed for maximum vertic expression. Four of the soils were dominated by smectitic minerals in the clay fraction while the rest exhibited a more mixed mineralogy. Disruption of illuvial clay features by shrink-swell movement was evident in thin section. Striated b-fabrics dominated the micromorphology except in non-expansive surface soils. K fixation of the soil surface was found to be negative in all soils, thus K fixation potential is considered very low. In subsurface horizons, K fixation generally increased with increasing vermiculite content. In addition to limited quantities of K-fixing clay minerals, naturally high K levels limited the amount of K fixation in this study. The information presented can be used to improve our understanding and management of high clay, vertic and claypan soils in southeastern Kansas.
Keywords: Vertic soils; Claypan soils; Soil genesis; Clay mineralogy; Soil micromorphology; Potassium fixation; Agriculture, Agronomy (0285); Agriculture, Soil Science (0481)